Microglial autophagy in cerebrovascular diseases - Chen, Man; Zhang, Hang; Chu, Yun-Hui; Tang, Yue; Pang, Xiao-Wei; Qin, Chuan; Tian, Dai-Shi (Frontiers in Aging Neuroscience, 2022)
Microglia are considered core regulators for monitoring homeostasis in the brain and primary responders to central nervous system (CNS) injuries. Autophagy affects the innate immune functions of microglia. Recently some evidence suggests that microglial autophagy is closely associated with brain function in both ischemic stroke and hemorrhagic stroke. Herein, we will discuss the interaction between autophagy and other biological processes in microglia under physiological and pathological conditions and highlight the interaction between microglial metabolism and autophagy. In the end, we focus on the effect of microglial autophagy in cerebrovascular diseases.